Frequency and cause of readmissions following pediatric otolaryngologic surgery. (12th November 2015) - Murray, Ryan; Logvinenko, Tanya; Roberson, David
Abstract : Objectives/Hypothesis: To characterize the frequency and nature of readmissions to free standing pediatric hospitals after otolaryngologic procedures. Study Design: Retrospective national database analysis. Methods: Using the Pediatric Health Information Systems database, we examined 30‐day inpatient readmissions in children less than 18 years old who underwent otolaryngology procedures between January 1, 2009, and December 31, 2011. Univariate and multivariate logistic regression analyses accounting for correlated structure of the data identified factors related to readmission rate. Reasons for readmission and the postoperative day at which readmission occurred were also examined. Results: In the 24‐month study period, a total of 493, 507 procedures were performed, resulting in 11, 574 (2.3%) 30‐day readmissions. Readmission rates varied significantly based on the type of procedure, patient age, and presence of chronic medical condition(s). Direct surgical complications accounted for 3, 432 (29.7%) of all readmissions; and 4, 729 (40.9%) of all readmissions occurred following tonsil and adenoid surgery. Conclusion: Readmissions after pediatric otolaryngologic surgery are relatively uncommon. These readmission rates vary directly with the type of procedure performed, as well as patient level factors (i.e., patient age, ethnicity, and the presence of other medical comorbidities). These data demonstrate that if readmission rates are to be used as a quality measure in pediatric otolaryngology procedures, complex risk adjustment of patient level variables will be necessary to accurately compare outcomes between different hospitals. Level of Evidence: 2c. Laryngoscope, 126:199–204, 2016